FEM-based analysis of avalanche ruggedness of high voltage SiC Merged-PiN-Schottky and Junction-Barrier-Schottky diodes. (November 2022) - Shen, Chengjun; Yu, Renze; Jahdi, Saeed; Mellor, Phil; Munagala, Sai Priya; Hopkins, Andrew; Simpson, Nick; Ortiz-Gonzalez, Jose; Alatise, Olayiwola
Abstract: Through comprehensive experimental measurements and TCAD simulation, it is shown that the avalanche ruggedness of SiC MPS & JBS diodes outperforms that of closely rated Silicon PiN diodes taking advantage of the wide-bandgap properties of SiC which leads to a high ionization and activation energy given the strong covalent bonds. Although the MPS diode structure favours a high reverse blocking voltage with small leakage current and a high current conduction, the localise current crowding caused by the multiple P + implanted region leads to the avalanche breakdown at lower load currents than the SiC JBS diode. The results of Silvaco TCAD Finite Element modellings have a good agreement with the experimental measurements, indicating that SiC JBS diode can withstand the high junction temperature induced by avalanche in line with the calculated avalanche energy. Highlights: SiC JBS diode withstand higher avalanche current than SiC MPS diode in different temperatures. Models indicate that SiC JBS diode withstand the highest temperature by the avalanche energy. TCAD models indicate that the Silicon PiN diode has failed by extreme electric field at the junction. The failure mechanism in the 4H-SiC MPS & JBS diodes are dominated by UIS heat generation.